Address before the Bankers' Club of Chicago, January 10, 1951 - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, echoed the Gordon Gray report regarding the importance of giving the underdeveloped countries a greater opportunity to raise their standard of living. He emphasizes the gradual nature of the development process and describes the obstacles which have to be overcome to accelerate it. He gives examples of Bank lending in support of development. He makes a case for providing grants instead of loans in some situations. He concludes that the United States and other industrial countries, in their own self-interest, should make additional financial and technical assistance available to the less developed countries of the world.